Zn0.4Cd0.4 COMPOSITE FABRICATION AND CHARACTERIZATION - Özkul, İskender; Biro, Safiye Jameel (My University, 2018)
ZnO-CdO composite was prepared with hydrothermal method. The structural,morphological, optical, and electrical properties of the nanocomposite have been carried out using X-raydiffraction (XRD), FTIR, scanning electron microscopy (SEM), UV-VIS-NIR spectrophotometer, and twoprobe, respectively. TG-DTA analysis was done to determine the thermal stability. The compositionalanalysis was done by EDX. The band gap of the composite were found to be 2.84 eV.
Keywords: Malzeme Bilimleri; Özellik ve Test; Malzeme Bilimleri; Biyomalzemeler